If I forget you : a novel - Greene, Thomas Christopher, 1968- (New York : Thomas Dunne Books/St. Martin's Press, 2016)
"Two former lovers reconnect in this beautiful and haunting tale of great lost love from the critically acclaimed author of The Headmaster's Wife -- Deeply affecting and compulsively readable, The Headmaster's Wife was a breakout book for Thomas Christopher Greene. Now, Greene returns with a beautifully written, emotional new novel perfect for his growing audience. Twenty-one years after they were driven apart by circumstances beyond their control, two former lovers have a chance encounter on a Manhattan street. What follows is a tense, suspenseful exploration of the many facets of enduring love. Told from altering points of view through time, If I Forget You tells the story of Henry Gold, a poet whose rise from poverty embodies the American dream, and Margot Fuller, the daughter of a prominent, wealthy family, and their unlikely, star-crossed love affair, complete with the secrets they carry when they find each other for the second time. Written in lyrical prose, If I Forget You is at once a great love story, a novel of marriage, manners, and family, a meditation on the nature of art, a moving elegy to what it means to love and to lose, and how the choices we make can change our lives forever"--
Keywords: Man-woman relationships -- Fiction; FICTION / Contemporary Women; FICTION / Literary; Romance fiction